Detection of Forged Images Using a Combination of Passive Methods Based on Neural Networks - Alencar, Ancilon Leuch (2024)
2020/09706-7) São Paulo Research Foundation (FAPESP), FAPESP–MCTIC-CGI.BR in partnership with Hapvida NotreDame Intermedica Group. Publisher Copyright: © 2024 by the authors.